2010
DOI: 10.1177/0963662510367571
|View full text |Cite
|
Sign up to set email alerts
|

Investigating CSI: Portrayals of DNA testing on a forensic crime show and their potential effects

Abstract: The popularity of forensic crime shows such as CSI has fueled debate about their potential social impact. This study considers CSI's potential effects on public understandings regarding DNA testing in the context of judicial processes, the policy debates surrounding crime laboratory procedures, and the forensic science profession, as well as an effect not discussed in previous accounts: namely, the show's potential impact on public understandings of DNA and genetics more generally. To develop a theoretical fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 42 publications
(50 reference statements)
1
47
0
3
Order By: Relevance
“…Thus, the hypothesis predicts that heavy use of media will be positively related to holding media-consistent beliefs, regardless of whether these media representations of reality are objectively correct. Scholars have found value in the cultivation approach for understanding media influence in many contexts, including science (30).…”
Section: Evidence Of Media Impactmentioning
confidence: 99%
“…Thus, the hypothesis predicts that heavy use of media will be positively related to holding media-consistent beliefs, regardless of whether these media representations of reality are objectively correct. Scholars have found value in the cultivation approach for understanding media influence in many contexts, including science (30).…”
Section: Evidence Of Media Impactmentioning
confidence: 99%
“…A série apresenta resoluções de crimes policiais com a ajuda de uma equipe de especialistas forenses que se utilizam de vários métodos, práticas e exames científicos. Tal programa vem fazendo bastante sucesso internacionalmente, causando o chamado "efeito CSI", caracterizado por uma apropriação de certos procedimentos científicos por parte de seus telespectadores (LEY, JANKOWSKI, BREWER, 2012;THOMAS, 2006). No Brasil, não é possível afirmar que a série terá efeitos similares ao que ocorre nos Estados Unidos.…”
Section: Discussão E Considerações Finaisunclassified
“…Além disso, estudos já mostram que o público está familiarizado com alguns procedimentos e métodos científicos mostrados em seriados televisivos, como é o caso do seriado CSI: Criminal Scene Investigation (THOMAS, 2006;COLE,DIOSO-VILLA, 2009;LEY, JANKOWSKI, BREWER, 2012). Siqueira (1998), Rondelli (2004) e Medeiros e colaboradores (2013), por sua vez, se dedicaram à análise de um dos programas de variedades mais duradouros da história da TV brasileira, o Fantástico, da Rede Globo.…”
unclassified
“…Based on a quantitative analysis of fifty-one randomly picked episodes from the first six seasons of CSI, Barbara Ley, Nathalie Jankowski and Paul R. Brewer have concluded that thirty-nine per cent of the episodes feature cases where DNA evidence is used to help solve the crime. 26 DNA evidence often figures as a kind of deus ex machina: it is the ultimate proof that forces the perpetrator to confess and swiftly removes any sense of confusion and doubt at the end of an episode. This narrative reliance on DNA evidence is not completely new.…”
Section: Sofia Bullmentioning
confidence: 99%